The Next Generation of Science Educators: Museum Volunteers. Issue 3 (3rd April 2022) - Refvem, Emma; Jones, M. Gail; Rende, K.; Carrier, Sarah; Ennes, Megan
ABSTRACT: There is a growing need for science educators and communicators who can support public understanding of complex science issues. Furthermore, little is known about how to nurture career aspirations for teaching science. This study examined the influence of youth volunteer experiences on career aspirations through a lens of science identity. Twenty-one participants were interviewed about high school volunteer experiences at a science museum. Data were coded for factors related to science identity (recognition, competence, and performance) and career aspirations. Results showed that the museum program contributed to the development of youth volunteers' science identities through experiences that bolstered individuals' science recognition, science competence, and science performance. Further analyses revealed the program's impact on the development of individuals' career interests in the areas of science communication and teaching. The results showed that after participating in the volunteer program, individuals indicated increased interests in communicating science to the public, teaching in informal science settings, and teaching in K-12 settings. These findings suggest that museum volunteer programs with an explicit focus on communicating science to the public may be optimal places to cultivate the next generation of science educators and communicators.